Analysis of anomalous CD44 gene expression in human breast, bladder, and colon cancer and correlation of observed mRNA and protein isoforms. - Woodman, A. C. (1996)
Many studies have now demonstrated disorganized overexpression of the CD44 gene in various types of human malignant tumors, and this abnormality has emerged as an interesting candidate marker for early cancer diagnosis. The purpose of this work was to analyze and compare the patterns of transcription and translation of this gene in human breast (ZR75-1; MDAMB-435 clone 4A4) and colon (HT29) tumor cell lines and in tumors of the breast, bladder, and colon, with the aim of identifying the most suitable analyte for diagnostic purposes. Transcription was studied by reverse transcription-polymerase chain reaction using CD44-specific primers and probes complementary to exons in the standard (exons 3 to 5 and 16 to 18) and variably expressed regions of this gene (exons 7, 8, 10, 11, and 15). Translation was investigated by Western blot analysis and immunohistochemistry using monoclonal antibodies specific to the standard form of CD44 and to the products of the same variant exons. Southern blot hybridization analysis of the reverse transcription-polymerase chain reaction products showed a large number of CD44 transcripts in tumor cells. Direct comparison of these Southern blots with Western blots on matched tumor-cell-line extracts indicated that most of the diverse mRNA isoforms did not detectably translate into proteins. However, immunohistochemistry of normal and malignant breast (n = 17 and 23, respectively), bladder (n = 5 and 19), and colon (n = 19 and 19) tissue specimens showed increased staining of CD44 standard and CD44 variant proteins in the carcinoma cells. Combination of this information with the data from reverse transcription-polymerase chain reaction and Western blot analysis indicates that the overexpression at the protein level involves only a minority of the aberrant RNA transcripts. We conclude that the development of methods for the accurate quantitation of over-abundant CD44 RNA species in clinical samples offers the most promising approach to improved early diagnosis of malignancy using this new marker.